Pauli blocking and medium effects in nucleon knockout reactions - Bertulani, C. A.; De Conti, C. [UNESP] (Amer Physical Soc, 2010)
We study medium modifications of the nucleon-nucleon (NN) cross sections and their influence on the nucleon knockout reactions. Using the eikonal approximation, we compare the results obtained with free NN cross sections with those obtained with a purely geometrical treatment of Pauli blocking and with NN obtained with more elaborated Dirac-Bruecker methods. The medium effects are parametrized in terms of the baryon density. We focus on symmetric nuclear matter, although the geometrical Pauli blocking also allows for the treatment of asymmetric nuclear matter. It is shown that medium effects can change the nucleon knockout cross sections and momentum distributions up to 10% in the energy range E(lab) = 50-300 MeV/nucleon. The effect is more evident in reactions involving halo nuclei.